2001
DOI: 10.1016/s0375-9601(01)00590-4
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on (1−q) expansion and factorization approximation in the Tsallis nonextensive statistical mechanics

Abstract: The validity of (1-q) expansion and factorization approximations are analysed in the framework of Tsallis statistics. We employ exact expressions for classical independent systems (harmonic oscillators) by considering the unnormalized and normalized constrainsts. We show that these approxiamtions can not be accurate in the analysis of systems with many degrees of freedom. I-IntroductionEver since the presentation by Tsallis[1, 2, 3] of a new possible generalization of the statistical mechanics (Tsallis statis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…(1) is supposed for composite systems containing N statistically independent subsystems in order to elicit the nonextensive character by following relation : (2) as one often finds in the literature. Due to this independence, it has been believed by many that exact calculations within NSM should use the additive hamiltonian H 0 = N n=1 H n , where H n is the hamiltonian of n th subsystem [2,[7][8][9][10][11]. However, this hamiltonian is not compatible with neither Eq.…”
Section: Factorization Of Compound Probability and Thermodynamicmentioning
confidence: 99%
“…(1) is supposed for composite systems containing N statistically independent subsystems in order to elicit the nonextensive character by following relation : (2) as one often finds in the literature. Due to this independence, it has been believed by many that exact calculations within NSM should use the additive hamiltonian H 0 = N n=1 H n , where H n is the hamiltonian of n th subsystem [2,[7][8][9][10][11]. However, this hamiltonian is not compatible with neither Eq.…”
Section: Factorization Of Compound Probability and Thermodynamicmentioning
confidence: 99%
“…Energy fluctuation in the canonical ensemble and ensemble equivalence in non-extensive statistics were investigated by Liyan and Julian using the generalized ideal gas and the generalized harmonic oscillators [10]. It has also been demonstrated that the (q-1) expansion on the factorization approximation is not useful for a system with N harmonic oscillators when one employs an arbitrary q and a very large N [19]. The sensitivity of the population of state to the value of q has been studied for some two-level model systems by considering the harmonic oscillator model and spin-1/2 [20].…”
Section: Introductionmentioning
confidence: 99%
“…. For the case previous works indicate that in the thermodynamic limit ( ∞ → N ) employing nonextensive statistical mechanics is not suitable to the classical ideal gas [34], the classical systems with N harmonic oscilators [38] and Fermi systems in a general power-law external potential [39]. Therefore, in this work, we consider only the case − .…”
Section: Nuclear Level Densitymentioning
confidence: 99%